2017
DOI: 10.12913/22998624/68283
|View full text |Cite
|
Sign up to set email alerts
|

Postbuckling Behaviour of Laminated Plates With a Cut-Out

Abstract: The subject of research is the numerical and experimental analysis of a thin-walled plate with the cut-out, made of the laminate and subjected to the axial compression. In order to ensure the stable plate work in the postcritical range, it need to force its work by higher flexural-torsional form of buckling. The scope of the research included nonlinear numerical analysis with Finite Element Method (FEM) and experimental verification of calculation results. For the composite material in numerical calculations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…6 show less stiffness than the results of the numerical calculations, however, the maximum differences do not exceed 27%. This fact results from the higher numerical model stiffness which preserves the ideal conditions of analysis, consistent with the results of similar studies published in existing literature [6,7]. …”
Section: Investigationssupporting
confidence: 91%
“…6 show less stiffness than the results of the numerical calculations, however, the maximum differences do not exceed 27%. This fact results from the higher numerical model stiffness which preserves the ideal conditions of analysis, consistent with the results of similar studies published in existing literature [6,7]. …”
Section: Investigationssupporting
confidence: 91%
“…FEM model was validated in experimental tests [2,4,5,6,7,16,17,18]. The C-section profile used during the experimental tests and the discrete model is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the research presented in [23] showed that the classic FEM approach to the analysis of post-critical behaviour, with the implemented higher buckling form, is inconsistent with real behaviour of the structure. However, due to the fact that the main assumptions remain in force, it was decided to search for a method to obtain the bending-twisting form as the lowest own form.…”
Section: Numerical Analysismentioning
confidence: 98%